Network Pharmacology-Based Strategy to Identify the Pharmacological Mechanisms of Pulsatilla Decoction against Crohn’s Disease - Liu, Jinguo; Zhang, Lu; Wang, Zhaojun; Chen, Shanshan; Feng, Shuyan; He, Yujin; Zhang, Shuo (Frontiers in Pharmacology, 2022)
Purpose: To explore the pharmacological mechanisms of Pulsatilla decoction (PD) against Crohn's disease (CD) via network pharmacology analysis combined with experimental validations. Methods: First, bioactive compounds and related targets of PD, as well as related genes of CD, were collected from public databases. Secondly, the drug-compound-target-disease network, the protein-protein interaction (PPI) network, Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses were performed to predict the core targets and pathways of PD against CD. Finally, the resected colonic tissues of CD patients and the CD fibrosis model of mice treated with PD were selected to verify the major targets predicted by network pharmacology. Results: By searching the intersection of the bioactive compounds targets and CD targets, a total of 134 targets were determined. The HSP90AA1 target was the common network core of the drug-compound-target-disease network and PPI network, which was used to simulate molecular docking with the corresponding bioactive compound. GO and KEGG enrichment analyses showed that the anti-fibrotic pathway was enriched by multiple targets and served as the target for experimental validation at patient and animal levels. The colon tissues of CD patients indicated that intestinal fibrosis in stenoses was more salient than non-stenoses with the upregulation of AKT, mTOR, PKCs and ERK1/2. The animal experiment revealed that colonic fibrosis mice with PD intervention had a lower degree of fibrosis than the model group with the downregulation of AKT, mTOR, PKCs and ERK1/2. Conclusion: We predicted the bioactive compounds and potential targets of PD intervention for CD through a network pharmacology approach, and some major targets in the predictive pathway were validated experimentally, which gave us a new perspective of the pharmacological mechanisms of PD in treating CD at the comprehensive levels.